2010
DOI: 10.1167/iovs.09-4001
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Intact Globe Expansion Method for Evaluation of Cross-linking Treatments

Abstract: The intact globe expansion method (GEM) imposes a loading geometry comparable to in vivo conditions and can quantify changes in mechanical stability as a function of testing conditions (e.g., IOP, tissue maturation, and therapeutic cross-linking) with small sample sizes and small variability. Rabbit kit eyes provide a model of weak tissue suitable for screening treatments that strengthen the cornea and sclera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…They reported that both riboflavin-UVA and glyceraldehyde cross-linking treatments reduced corneal expansion, implying increased mechanical stability. 17 In contrast to these in vitro studies, in our study, we did not observe significant changes in biomechanical properties of the cornea after CXL for keratoconus as measured in vivo by ORA. We previously published similar results after 6 months of follow-up.…”
Section: Discussioncontrasting
confidence: 98%
“…They reported that both riboflavin-UVA and glyceraldehyde cross-linking treatments reduced corneal expansion, implying increased mechanical stability. 17 In contrast to these in vitro studies, in our study, we did not observe significant changes in biomechanical properties of the cornea after CXL for keratoconus as measured in vivo by ORA. We previously published similar results after 6 months of follow-up.…”
Section: Discussioncontrasting
confidence: 98%
“…In a comparison of uniaxial testing and whole globe inflation of porcine eyes (Lari et al 2012) found smaller extensibility and larger stress-induced stiffening with whole eye preparations. For these reasons, whole globe testing is becoming increasingly common, with recently published studies investigating bovine scleral biomechanics (Myers et al 2010) and the effects of scleral cross-linking treatments on rabbit eyes (Mattson et al, 2010). This approach has also been used to study age-related changes at the optic nerve head (Girard et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Viscoelastic tensile creep and relaxation tests have also been conducted on these tissues [21,[23][24][25]. Inflation tests wherein whole [19,[26][27][28][29][30][31] or partial globes [32][33][34][35][36][37] are subjected to increasing levels of pressure while the scleral surface is imaged have been used to study the sclera's strain field, viscoelasticity, and the effects of various eye disease treatments. In general, these types of tests, particularly those on whole globes, are more physiologically realistic than tests on excised specimens.…”
Section: Introductionmentioning
confidence: 99%